STUDI KUALITATIF TENTANG IMPLEMENTASI PROFESIONALISME GURU DALAM PELAKSANAAN PEMBELAJARAN DI SEKOLAH MENENGAH - Ayuni Setiawati; Kartini Rahman Nisa (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Improvements in the quality of human resources are greatly influenced by the quality of education, in which teachers play an important role indetermining the effectiveness of the learning process. Although teacher competency standards have been established through Law No. 14 of 2005, studies that describe the implementation of teacher professionalism based on direct experience in schools are still limited. Therefore, this study aims to describe and understand teacher professionalism based on teachers' experiences and perspectives in carrying out their duties at school. This study uses a qualitative approach with semi-structured interview techniques and documentation of teachers as research subjects. The results of the study show that teachers have implemented pedagogical, professional, social, and personal competencies in an integrated manner in their teaching practices. The integration of these four competencies supports the creation of effective, meaningful learning that is oriented towards developing the potential and character of students. It is concluded that teacher professionalism is reflected through the comprehensive application of the four competencies in the performance of their duties, thereby contributing to improving the quality of learning.